Arbitration and Dispute Resolution in the Resources Sector: An Australian Perspective - Moens, Gabriël A (Springer, 2016)
This book provides a comprehensive Australian perspective on the resolution of resources disputes. In particular, it focuses on the use of arbitration, mediation and adjudication in the resources sector. It concentrates on arbitration as the preferred method of dispute resolution, including international commercial and investor-state arbitration. The book offers fascinating insights into the use of arbitration to investment disputes involving resources companies in the African OHADA countries, Australia and other countries. It offers an Australian perspective which will be useful to discerning arbitration scholars and dispute resolvers. In addition, the book provides useful information on how to draft arbitration clauses for resources sector contracts. This publication will be of interest to members of the academic research community and will also appeal to dispute resolution professionals and practitioners.